A real-time PCR assay to differentiate the B and Q biotypes of the Bemisia tabaci complex in Cyprus - Papayiannis, Lambros C.; Brown, Judith K.; Seraphides, Nicos A.; Hadjistylli, Margarita; Katis, Nikolaos I.; Ioannou, Nicolas (My University, 2009)
A real-time PCR assay based on TaqMan® technology was developed and evaluated for the rapid detection of the B and Q biotypes of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae). A survey was conducted during 2005-2007 in order to identify the distribution and prevalence of B. tabaci biotypes in Cyprus using the real-time PCR assay. More than 700 adult whiteflies collected from 35 cultivated and weed plant species were individually haplotyped using TaqMan® PCR, and the results of the assay were validated by restriction fragment length polymorphism analysis and DNA sequencing of the mitochondrial cytochrome oxidase I (mtCOI) gene. Two biotypes, B and Q, were identified in the collected plant species on the island. The real-time PCR and RFLP assay consistently yielded the same results, although the real-time assay was more sensitive and less time consuming. Phylogenetic analysis of the mtCOI DNA sequences corroborated the identity of the B and Q biotypes 100% of the time and by phylogenetic analysis the haplotypes grouped, as expected, in the major North African-Mediterranean-Middle Eastern clade of the B. tabaci complex.
Keywords: Bemisia tabaci complex; Haplotype; Mitochondrial COI gene; Real-time PCR; RFLP analysis